Urothelial Cell Carcinoma of the Bladder and Urinary Bladder Rupture as a Rare Cause of Acute Peritonitis: A Case Report - Johnson Da Huang; Emily Ximin Shao; Alexander Ngoo; Chui Ming Tham; Handoo Rhee (Case Reports in Acute Medicine, 2024)
Introduction: Urothelial carcinoma of the bladder causing spontaneous rupture of the bladder is an extremely rare condition with poor outcomes due to it being highly suggestive of advanced malignancy. Case Presentation: We present the case of a 74-year-old man who presented with non-specific signs and symptoms of abdominal pain and haematuria. Abdominal imaging was suggestive of a small bowel obstruction and a bowel perforation. At time of laparotomy, however, the patient was found to have metastatic urothelial carcinoma with peritoneal metastases. The patient unfortunately passed away 2 months following their initial presentation. Conclusion: Bladder perforation secondary to urothelial cancer is a rare pathology associated with poor prognosis. There are fewer than thirty cases reported in the literature, and it is often not considered during initial diagnostic workup of patients with abdominal sepsis in the context of bladder cancer. A high degree of suspicion for bladder rupture is recommended in patients with peritonism and urinary symptoms. Awareness of this condition will help facilitate prompt diagnosis and appropriate management.